h - Lee, Jimmy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 17th International Conference on Principles and Practice of Constraint Programming, CP 2011, held in Perugia, Italy, September 12-16, 2011. The 51 revised full papers and 7 short papers presented together with three invited talks were carefully reviewed and selected from 159 submissions. The papers are organized in topical sections on algorithms, environments, languages, models and systems, applications such as decision making, resource allocation and agreement technologies.
Keywords: Computer science; Computer software; Logic design; Artificial intelligence; Computer Science; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Artificial Intelligence (incl. Robotics).; Programming Languages, Compilers, Interpreters; Computation by Abstract Devices